Electroporation-Based Treatments in Urology - Kiełbik, Aleksander (Cancers (Basel), 2020)
The observation that an application of a pulsed electric field (PEF) resulted in an increased permeability of the cell membrane has led to the discovery of the phenomenon called electroporation (EP). Depending on the parameters of the electric current and cell features, electroporation can be either reversible or irreversible. The irreversible electroporation (IRE) found its use in urology as a non-thermal ablative method of prostate and renal cancer. As its mechanism is based on the permeabilization of cell membrane phospholipids, IRE (as well as other treatments based on EP) provides selectivity sparing extracellular proteins and matrix. Reversible EP enables the transfer of genes, drugs, and small exogenous proteins. In clinical practice, reversible EP can locally increase the uptake of cytotoxic drugs such as cisplatin and bleomycin. This approach is known as electrochemotherapy (ECT). Few in vivo and in vitro trials of ECT have been performed on urological cancers. EP provides the possibility of transmission of genes across the cell membrane. As the protocols of gene electrotransfer (GET) over the last few years have improved, EP has become a well-known technique for non-viral cell transfection. GET involves DNA transfection directly to the cancer or the host skin and muscle tissue. Among urological cancers, the GET of several plasmids encoding prostate cancer antigens has been investigated in clinical trials. This review brings into discussion the underlying mechanism of EP and an overview of the latest progress and development perspectives of EP-based treatments in urology.